ENVIRAD – A Database Integration for Environmental Samples Radiological Data - Sergio de Albuquerque Gonzalez; Tadeu Augusto de Almeida Silva; Claudio de Carvalho Conti; Iolanda Osvath; Hussein Ramadan; Jean Bartocci (Brazilian Journal of Radiation Sciences, 2020)
With the increasing use of databases for environmental radiological monitoring in soils, food, water and sediments, among others, there is a demand for integrating this kind of information availability, aiming at a data management for greater searchability for the most varied purposes. ENVIRAD is a proposal to integrate these databases, providing researchers with a tool for a more complete analysis of the environment’s study. ENVIRAD, as developed so far, works with the integration of the following databases: MARIS, GLOMARD, GEORAD and SIGLARA databases, enabling queries and demonstrating great potential in the use of data integration for environmental samples.